Evaluasi Fungsi Kontra Intelijen Indonesia Dalam Menghadapi Spionase Intelijen Asing - Kuswara, Yosa Bayu (Jurnal Kajian Stratejik Ketahanan Nasional, 2019)
Espionage is an information gathering methode conducted by intelligence services both in intelligence acivities or closed/clandestine operations using open or closed tactics With its huge valuable resources, Indonesia becomes attractive for great powers intervention. Such a condition creates a threat to Indonesia national resiliency, especially threats from espionage activities. These threats should be seriously handled by the Indonesian government. Empirical cases of strategic surprises have suggested the role of foreign intelligence in Indonesia. Despite the fact that Indonesia has several intelligence agencies and some of them have conducted counter intelligence activities, Indonesia has yet had specific agency that deals with espionage activties. This theses is aiming at evaluating the need to establish such an agency. Using scenario building method and combined with threat analysis, this theses finds that the current capability of Indonesian intelligence agencies in dealing with espionage activities is less than ideal while the threat of foreign espionage activities is high.